Analysis of legal aspects in online sale and purchase agreements in the digital era challenges and consumer protection - Pratama, Najar; Hifni, Mohammad (Journal of Law Science, 2024)
In the rapidly evolving digital age, online buy and sell agreements are becoming increasingly common and important. However, this phenomenon faces various legal challenges that need to be addressed to protect consumers and ensure legal compliance. This article analyzes the legal aspects of online buy and sell agreements with a focus on emerging challenges and consumer protection mechanisms. First, it identifies the main challenges faced in online buy and sell agreements, including issues related to the validity of electronic contracts, enforcement of the rights and obligations of the parties, and the risk of fraud and misuse of personal data. Next, it explores the various forms of consumer protection available in the digital era, such as personal data protection regulations, provisions on the right to return goods, and policies on information transparency. The analysis is based on a review of applicable laws in various jurisdictions as well as best practices adopted by e-commerce platforms. With an in-depth understanding of these legal aspects, this article aims to provide insights for policymakers, businesses, and consumers in effectively and safely managing and navigating online buying and selling agreements.